Method for improving strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation and high-plasticity TiAl alloy
By performing multiple axial compression of TiAl alloy based on cooling and isothermal superposition deformation, the problem of insufficient plasticity and processing performance under room temperature and thermal processing conditions is solved, and nano-shaped β0 phase and γ phase recrystallization is achieved. The mechanical properties and processing stability of the alloy are significantly improved.
Patent Information
- Application Number
- CN202411115940.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The plasticity and processing performance of TiAl-based alloys under room temperature and thermal processing conditions are poor, mainly due to the inappropriate refinement of the brittle β0 phase and the grains of the lamella.
Using a method based on cooling and isothermal superposition deformation, the TiAl alloy is compressed multiple times in axial direction, gradually reducing the set temperature and compression ratio, and retaining micro/nano defects such as nanotwins and dislocations to room temperature to promote the B2 phase. Nanoization and dynamic recrystallization of gamma phase.
The room temperature and high temperature plasticity of TiAl alloy is significantly improved, its mechanical properties are enhanced, cracking problems caused by uneven heat treatment is avoided, the process flow is simplified and energy consumption is reduced.
Smart Images

Figure CN119162525A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature light alloy processing, and specifically relates to a method for improving the strength and plasticity of a TiAl alloy based on cooling and isothermal superimposed deformation, and a strong-plastic TiAl alloy. Background Art
[0002] γ-TiAl-based alloys have lower density and specific strength, and their high temperature strength, creep resistance and oxidation resistance have considerable development potential. However, one of the biggest obstacles restricting the practical application and promotion of TiAl-based alloys is their poor room temperature plasticity and hot workability.
[0003] The lamellar clusters with different orientations and a large amount of brittle β0 phase are the main limiting factors. The forging and rolling composite technology can effectively refine the grains to improve the room temperature plasticity, but the high deformation temperature has high requirements on the equipment and the controllability of the deformation parameters is poor. High temperature and long time heat treatment can eliminate the β0 phase, but it also inhibits the lubrication effect of the B2 phase under high temperature deformation conditions. Therefore, how to promote the nano-development of the β0 phase at the boundary of the lamellar cluster while slightly refining the size of the lamellar cluster is a problem worth exploring. This method combines the advantages of coarse grains and fine grains, so that the alloy contains rich nanostructures, which will help to improve the shortcomings of TiAl alloys at room temperature and hot working conditions. Some literatures disclose a scheme for refining alloy grains by low temperature pre-deformation and isothermal heat treatment, but the isothermal heat treatment temperature (1280-1320℃) is higher than the pre-deformation temperature (900℃), and the grains are easy to grow under high temperature and long time heat treatment conditions, thereby weakening the refining effect of pre-deformation on the grains. Other documents disclose that only fine lamellar structures exist in TiAl alloys through creep forming and heat treatment. Although this method helps to improve room temperature ductility, the beneficial effect of β0 on hot working performance is also suppressed. In addition, microstructures with heterogeneous structures can be designed and prepared by powder metallurgy, but the mechanical properties of the prepared alloys are unstable due to the influence of alloy powder quality and porosity.
[0004] Therefore, there is an urgent need to find a processing method that is technically stable, can significantly reduce the size of the brittle β0 phase, and does not over-refine the lamellar grains, so as to effectively improve the room temperature plasticity and hot working properties of TiAl alloys. Summary of the invention
[0005] The object of the present invention is to provide a method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation and a strong-plastic TiAl alloy, so as to help stably improve the room temperature plasticity and / or hot working properties of the TiAl alloy.
[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superimposed deformation, comprising the following steps: performing multiple axial compressions on a sample of a TiAl alloy ingot; before each compression, heating the sample to a set temperature and keeping the temperature, then compressing it, and cooling it to room temperature after each compression; as the number of compressions increases, the set temperature gradually decreases, the compression ratio gradually decreases, or the compression ratio is first maintained unchanged and then gradually decreased.
[0007] Preferably, the set temperature is the transition temperature T at which the sample transforms from the γ phase to the α phase. e The temperature value is below the lower limit temperature; the cooling method is air cooling.
[0008] Preferably, the number of compressions is 3-7 times, the difference in set temperatures before two adjacent compressions is 10-100°C; the difference in ratios between two adjacent compressions is 0-15%, and the difference in ratios between two adjacent compressions first increases and then decreases as the number of compressions increases.
[0009] Preferably, the set temperature is 1170-1220°C, 1130-1170°C, 1080-1130°C, 1030-1080°C and 930-980°C respectively as the number of compressions increases; calculated based on the initial height of the sample, the compression ratio is 22%-27%, 22%-27%, 12%-17%, 7%-12% and 3%-7% respectively as the number of compressions increases.
[0010] Preferably, the compression rate is 0.001-0.05s each time. -1 ; The insulation time is 10-30min.
[0011] Preferably, the heating and compressing are performed under vacuum conditions in a heating furnace of a universal testing machine.
[0012] Preferably, the sample is cylindrical, a positive thermocouple and a negative thermocouple are welded on the sample, and the upper and lower end surfaces of the sample are respectively in close contact with the nickel-based alloy pads of the universal testing machine; in the height direction of the sample, the positive thermocouple and the negative thermocouple are arranged at the center of the sample.
[0013] Preferably, the element composition of the TiAl alloy ingot comprises, in atomic percentage, 46%-50% Al, 2%-6% Cr, 0.2%-1.2% Re and 0-2% Ru.
[0014] Preferably, the TiAl alloy ingot is obtained by vacuum arc melting; the raw materials of the TiAl alloy ingot include: sponge Ti particles or sponge Ti blocks; Al particles, the particle size of the Al particles is 2-3mm, and the purity is 99.99wt.%; Cr particles, the particle size of the Cr particles is 2-3mm, and the purity is 99.99wt.%; Ru powder, the purity of the Ru powder is 99.999wt.%; Re powder, the purity of the Re powder is 99.999wt.%.
[0015] The present invention also provides a high-plasticity TiAl alloy, which adopts the following technical solution: a high-plasticity TiAl alloy, wherein the high-plasticity TiAl alloy is processed by the method as described above.
[0016] Beneficial effects:
[0017] The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superimposed deformation is technically stable, can significantly reduce the size of the brittle β0 phase, and does not excessively refine the lamellar cluster grains, and can effectively improve the room temperature plasticity and hot working properties of TiAl alloy.
[0018] The method of improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention can retain the micro / nano defects such as nano twins and dislocations formed in the TiAl alloy after each compression, and will not be annihilated due to the temperature increase again. Therefore, the alloy sample finally prepared accumulates abundant micro-nano defects, and these nanostructures are conducive to activating more dislocation slips and fully coordinating the plastic deformation of the alloy under the action of external forces.
[0019] The present invention uses the method of sequential cooling and isothermal axial compression to promote the corresponding changes in the microstructure of the TiAl alloy under different compression conditions, that is, micro-nano defects are continuously accumulated (these abundant defects are channels for dislocation slip, are nucleation sites for stacking faults and nano twins, and are important factors for improving the room temperature and high temperature plasticity of the alloy), the lamellar cluster grains are refined, the B2 phase is gradually nano-sized, and the equiaxed γ phase is dynamically recrystallized. These microstructural changes provide space for improving room temperature plasticity and hot working properties.
[0020] The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation provided by the present invention combines heat treatment and thermal deformation at the same time, so that the alloy undergoes timely heat preservation and low-degree deformation at a temperature lower than the γ→α phase transition, thereby avoiding cracking of the alloy caused by uneven heating and severe deformation. The compression deformation temperature and deformation amount are sequentially reduced to ensure that the micro-nano defects induced by each compression deformation are retained, which is beneficial to improving the room temperature and high-temperature plasticity of the alloy below 950°C.
[0021] The preparation method provided by the present invention has simple process, the heating and holding time can be accurately set by a computer, the preparation process has low cost and low energy consumption, and a plurality of deformed alloy samples can be quickly prepared.
[0022] The method of improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention can make the prepared strong plastic TiAl alloy have good room temperature compression and high temperature tensile properties. This deformation method that improves both strength and plasticity enriches the hot processing technology of TiAl alloy, improves the shortcomings of TiAl alloy in room temperature plasticity, and is expected to promote the multi-directional application of TiAl alloy in military fields such as aerospace, automobiles and aircraft.
[0023] The high-plasticity TiAl alloy of the present invention has a network structure formed by nano B2 phase and equiaxed γ phase wrapping fine lamellar clusters. Compared with the cast TiAl alloy, the room temperature compressive strength is increased from 1919.4MPa to 2536.5MPa, and the compressive strain is significantly increased from 32.9% to 42.6%; at 850°C, the tensile strength of the TiAl alloy is increased from 403.5MPa to 505.7MPa, and the elongation is increased from 3.5% to 5.3%, and the room temperature and high temperature mechanical capabilities of the alloy are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0025] Figure 1 This is a flow chart of a method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation according to an embodiment of the present invention;
[0026] Figure 2 The figures are comparison diagrams of the macroscopic structure photographs of the TiAl alloy of Comparative Example 1 and Example 1; wherein (a) is the macroscopic structure photograph of the TiAl alloy of Comparative Example 1, and (b) is the macroscopic structure photograph of the high-plasticity TiAl alloy of Example 1;
[0027] Figure 3 The figures are comparison diagrams of the macroscopic structure photographs of the TiAl alloy of Comparative Example 2 and Example 1; wherein (a) is the macroscopic structure photograph of the TiAl alloy of Comparative Example 2, and (b) is the macroscopic structure photograph of the high-plasticity TiAl alloy of Example 1;
[0028] Figure 4 The microstructure photos of TiAl alloy under the original casting condition; (a) is a scanning electron microscope image, and (b) is a local magnified image of the red box area in (a);
[0029] Figure 5 At 1200℃, in 0.01s -1 Microstructure group pictures of TiAl alloy obtained after keeping warm for 20 minutes and pressing down to 25% of the original height under a constant strain rate of ; (a) is a scanning electron microscope image, and (b) is a local magnified image of the red box area in (a);
[0030] Figure 6 At 950℃, in 0.01s -1 Microstructure of the TiAl alloy obtained after 20 min of holding at a constant strain rate and further compression by 5% of the original height after the first four compression deformations; (a) is a scanning electron microscope image, (b) is a local magnified image of the red box area in (a); (c) is a transmission electron microscope bright field image of dislocations and nanotwins in the TiAl alloy after deformation;
[0031] Figure 7 1 is a graph showing the mechanical properties test results of the TiAl alloys in the comparative examples and the embodiments; wherein, (a) is the room temperature compression test result of the original cast TiAl alloy, the TiAl alloys of comparative examples 1-4 and the high-plasticity TiAl alloy of embodiment 1; (b) is the tensile test result of the original cast TiAl alloy, the TiAl alloys of comparative examples 1-4 and the high-plasticity TiAl alloy of embodiment 1 at 850°C. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0033] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0034] The present invention aims at at least one of the problems that the current TiAl alloy has poor room temperature plasticity and / or hot working performance, the existing process has limited effect on improving the room temperature plasticity and / or hot working performance of the TiAl alloy, and the existing improvement process has poor stability. A method for improving the high plasticity of the TiAl alloy based on cooling and isothermal superimposed deformation and a high-plasticity TiAl alloy are provided.
[0035] The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation according to the embodiment of the present invention comprises the following steps: subjecting the sample of TiAl alloy ingot to multiple axial compressions, heating the sample to a set temperature and keeping it warm before each compression, and then compressing it, and cooling it to room temperature after each compression; as the number of compressions increases, the set temperature gradually decreases, the compression ratio gradually decreases, or the compression ratio is maintained unchanged and then gradually decreases. Among them, there are two purposes for cooling to room temperature after each compression: on the one hand, cooling to room temperature can obtain room temperature structure, which is more stable. If cooled to a higher temperature, the retained structure is a metastable structure, and the microstructure and mechanical properties are unstable; on the other hand, cooling to room temperature after each compression is convenient for comparing microstructures, and there is no variable such as cooling temperature.
[0036] The method of the present invention can not only slightly refine the size of the lamellar clusters and retain a small amount of B2 phase, but also retain nanostructures such as dislocations and nano twins when transforming the original cast structure (TiAl alloy ingot) (the method of the present invention can retain the micro / nano defects such as nano twins and dislocations formed in the TiAl alloy after each compression deformation, and will not be annihilated due to the temperature increase again. Therefore, the alloy sample finally prepared accumulates rich micro-nano defects, and these nanostructures are conducive to activating more dislocation slips and fully coordinating the plastic deformation of the alloy under external forces). The present invention adopts the method of sequential cooling and isothermal axial compression to promote the corresponding changes in the microstructure of the TiAl alloy under different deformation conditions, that is, micro-nano defects continue to accumulate, the lamellar cluster grains are refined, the B2 phase is gradually nano-sized, and the equiaxed γ phase is dynamically recrystallized. These microstructural changes provide space for improving room temperature plasticity and hot working properties. Among them, the set temperature (i.e., the compression temperature of the sample) and the compression ratio are successively reduced to ensure that the micro-nano defects induced by each compression deformation are retained, which is beneficial to improving the room temperature and high-temperature plasticity of the alloy below 950°C.
[0037] In addition, the present invention realizes large plastic deformation by compressing the cast TiAl alloy in steps, thereby avoiding excessive work hardening and cracking of the alloy during a single deformation process, helping to reduce stress concentration and ensure macroscopic uniformity of the microstructure.
[0038] The present invention accumulates micro-nano defects generated during each cooling-isothermal deformation process by sequentially cooling and then isothermally compressing at the temperature. These abundant defects are channels for dislocation slip, and are nucleation sites for stacking faults and nano twins, which are important factors for improving room temperature and high temperature plasticity of alloys. The method of the present invention is simple and convenient, and the heating and holding time can be accurately set by a computer. The preparation process has low cost, low energy consumption, and high efficiency (multiple samples can be processed quickly).
[0039] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the set temperature is based on the transition temperature T of the sample from the γ phase to the α phase. e The lower and upper temperature limits are determined by the γ phase transformation into the α phase.
[0040] Preferably, the set temperature is the transition temperature T at which the sample transforms from the γ phase to the α phase. e The method of improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention combines heat treatment and thermal deformation at the same time, so that the alloy undergoes timely heat preservation and low-degree deformation at a temperature lower than the γ→α phase transition, thereby avoiding cracking of the alloy caused by uneven heating and severe deformation. In addition, by setting the set temperature below T e The lower limit temperature (i.e., lower than the minimum temperature at which the γ phase transforms to the α phase) helps to ensure that the TiAl alloy does not undergo a γ→α phase transformation during deformation, so that there is enough γ phase to form a large number of nano-defects such as dislocations and nano-twins.
[0041] Preferably, T e The lower limit temperature is -10℃≤set temperature≤T e The lower limit temperature is -300℃.
[0042] In the preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the cooling method is air cooling. Among them, the cooling method or rate has a greater impact on the microstructure of TiAl alloy; when water cooling or a higher cooling rate is used, the solidification path of the alloy tends to deviate from the equilibrium solidification to a higher degree, so metastable phases or intermediate phases will be formed. Due to their instability, the microstructure and mechanical properties of the alloy are greatly affected by temperature or solidification rate. Secondly, the phase change stress generated by the excessively high cooling rate is greater, which may cause the alloy to crack; and a smaller cooling rate will increase the grain size in the alloy, resulting in a coarse microstructure of the alloy, and due to the lower driving force, the formation conditions of some precipitation phases may not be met, and the mechanical properties of the alloy cannot be further enhanced.
[0043] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the number of compressions is 3-7 times, the difference in set temperature before two adjacent compressions is 10-100°C; the difference in the ratio of two adjacent compressions is 0-15%, and as the number of compressions increases, the difference in the ratio of two adjacent compressions first increases and then decreases. Among them, the number of compressions will affect the performance of TiAl alloy, because the increase in the number of compressions will further refine the microstructure of the alloy, but this kind of microstructure refinement has limited improvement on mechanical properties. Beyond a certain range, the microstructure refinement brought about by more compressions has little effect on mechanical properties.
[0044] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the set temperature is 1170-1220°C (for example, 1170°C, 1180°C, 1190°C, 1200°C, 1210°C or 1220°C), 1130-1170°C (for example, 1130°C, 1140°C, 1150°C, 1160°C or 1170°C), 1080-1130°C (for example, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C or 1130°C), 1030-1080°C (for example, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C or 1080°C) 80℃) and 930-980℃ (for example, 930℃, 940℃, 950℃, 960℃, 970℃ or 980℃); based on the initial height of the sample, the compression ratio is 22%-27% (for example, 22%, 23%, 24%, 25%, 26% or 27%), 22%-27% (for example, 22%, 23%, 24%, 25%, 26% or 27%), 12%-17% (for example, 12%, 13%, 14%, 15%, 16% or 17%), 7%-12% (for example, 7%, 8%, 9%, 10%, 11% or 12%) and 3%-7% (for example, 3%, 4%, 5%, 6%, or 7%) as the number of compressions increases. The method of the present invention enables the TiAl alloy to be pressed down to 80% of the original height under the conditions of multiple cooling and isothermal superposition (if not limited by the experimental equipment itself, the TiAl alloy can undergo more than 80% plastic deformation by adopting this deformation method); timely heat preservation is performed before each isothermal compression, and the pressing amount is reduced successively, which effectively avoids the TiAl alloy from cracking due to stress concentration.
[0045] In the preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the number of compressions is 5 times, and the set temperatures are 1200°C, 1150°C, 1100°C, 1050°C and 950°C in sequence as the number of compressions increases; based on the initial height of the sample, the compression ratio is 25%, 25%, 15%, 10% and 5% in sequence as the number of compressions increases. The method of the present invention allows the TiAl alloy to be pressed down by 80% of the original height under the conditions of multiple cooling and isothermal superposition; timely heat preservation is carried out before each isothermal compression, and the amount of pressing is reduced in sequence, which effectively avoids the cracking of the TiAl alloy due to stress concentration. If not limited by the experimental equipment itself, the TiAl alloy can undergo more than 80% plastic deformation using this deformation method. In this preferred embodiment, the step of compressing at 1000°C is omitted; however, when the compression temperature is reduced from 1050°C to 950°C (i.e., the temperature is reduced by 100°C), the TiAl alloy still has good plastic deformation ability and does not crack. In addition, the step of compressing at 1000°C can be added as needed.
[0046] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the compression rate of each time is 0.001-0.05s -1 (For example, 0.001s -1 、0.003s -1 , 0.005s -1 、0.008s -1 、0.01s -1 、0.02s -1 、0.03s -1 、0.04s -1 or 0.05s -1 ); the holding time is 10-30min (for example, 10min, 15min, 20min, 25min or 30min). Among them, the compression rate is one of the important factors affecting the mechanical properties of the alloy. It mainly affects the mechanical properties of the alloy such as yield strength, compressive strength and plasticity by affecting the dislocation movement, solute atom diffusion and microstructure evolution inside the alloy; in TiAl alloy, a reasonable compression rate range can significantly improve the plasticity and yield strength of the alloy. The holding time will affect the microstructure, mechanical properties and possible defect formation of the alloy; with the increase of the holding time, the physical phase inside the alloy can gradually transform into a more stable γ phase, and the fracture mechanism of the alloy may also change from brittle fracture to nucleation and aggregation of pores. In addition, too long a holding time may cause microcracks inside the TiAl alloy. Therefore, the compression rate and holding time during deformation of TiAl alloy should be reasonably controlled.
[0047] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, heating and compression are performed in a heating furnace of a universal testing machine under vacuum conditions. The present invention integrates heat treatment technology and thermal deformation technology (heating and compression of the sample are both performed in a universal testing machine), avoiding heat dissipation when the TiAl alloy is transferred from a variety of devices. Each step of the deformation operation is independent, and the actual temperature of the sample during compression deformation can be accurately evaluated, ensuring that the TiAl alloy undergoes stable plastic deformation at a stable deformation temperature.
[0048] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superimposed deformation of the present invention, the sample is cylindrical, a positive thermocouple and a negative thermocouple are welded on the sample, and the upper and lower end surfaces of the sample are respectively tightly attached to the nickel-based alloy pads of the universal testing machine; in the height direction of the sample, the positive thermocouple and the negative thermocouple are arranged at the center of the sample.
[0049] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the element composition of the TiAl alloy ingot includes, in atomic percentage, Al 46% to 50%
[0050] (e.g., 46%, 47%, 48%, 49% or 50%), Cr 2% to 6% (e.g., 2%, 3%, 4%, 5% or 6%), Re 0.2% to 1.2% (0.2%, 0.4%, 0.6%, 0.8%, 1.0% or 1.2%) and Ru 0 to 2% (e.g., 0, 0.4%, 0.8%, 1.2%, 1.6% or 2%). Among them, the appropriate amount of Cr element can refine the microstructure of the alloy and improve the strength and plasticity of the alloy; the Re element helps to improve the metallurgical quality of the TiAl alloy, reduce defects and impurity content, and improve the overall performance and reliability of the alloy; the Ru element promotes the formation of the B2 phase, helps to improve the microstructure, and the appropriate amount of Ru element can also stabilize the microstructure of the alloy, prevent the precipitation of harmful phases, and thus improve the high-temperature mechanical properties of the alloy; the Al element is the basic element of the TiAl alloy, and Al combines with Ti to form intermetallic compounds TiAl and Ti3Al with high strength; in addition, different contents of Al elements will make the alloy have different solidification structures, because the Al content will affect the physical phase composition of the alloy. Therefore, in the present invention, the Al content changes from 46% to 50%, and the corresponding alloy will experience different solidification paths, resulting in different room temperature solidification structures, but within the Al content range, the alloy can be compressed and deformed by the method of the present invention, indicating that its microstructure has good compatibility with deformation. Al in TiAl alloy has a significant impact on the performance of the alloy by strengthening, reducing density, improving thermal stability, improving weldability, improving oxidation resistance, and affecting crack propagation mechanism and mechanical properties.
[0051] It should also be noted that the method of improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention is also applicable to other titanium aluminum alloys with different elemental compositions from the above preferred embodiments. This is because the method of the present invention adopts a slower compression rate, proper heat preservation before each compression, and a smaller deformation amount for each compression. Therefore, even if the microstructure of the alloy is slightly different under different Al contents, such a deformation method can effectively avoid cracking and high work hardening of the alloy, help the alloy to continue to undergo plastic deformation, and is less sensitive to the microstructure.
[0052] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superimposed deformation of the present invention, the TiAl alloy ingot is obtained by vacuum arc melting; the TiAl alloy ingot is obtained by vacuum arc melting; the raw materials of the TiAl alloy ingot include: sponge Ti particles or sponge Ti blocks; Al particles, the particle size of the Al particles is 2-3mm, and the purity is 99.99wt.%; Cr particles, the particle size of the Cr particles is 2-3mm, and the purity is 99.99wt.%; Ru powder, the purity of Ru powder is 99.999wt.%; Re powder, the purity of Re powder is 99.999wt.%.
[0053] In a preferred embodiment of the method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation of the present invention, the preparation of TiAl alloy ingot comprises the following steps:
[0054] (1) Melting: Wrap Re powder and Ru powder with aluminum foil and place them at the bottom of a water-cooled copper crucible in a vacuum arc melting furnace, spread Al particles and Cr particles on top of the aluminum foil, place a titanium sponge block on top of the crucible, close the door of the vacuum arc melting furnace, and turn on the circulating cooling water;
[0055] (2) Vacuum treatment: evacuate the vacuum arc melting furnace to 3×10 -3 Pa, high-purity argon gas is filled into the vacuum arc melting furnace until the pressure inside the furnace reaches 0.05Pa;
[0056] (3) Arc heating and melting:
[0057] A. After ignition, increase the current from 30A to 150A to soften the raw materials and connect them to each other, then increase the current evenly to 550A to melt all the raw materials completely to form a uniform melt, then slowly reduce the current to 0A, turn off the power, and the first smelting is completed;
[0058] B. After the melt obtained by the first smelting solidifies and forms, it is turned over and smelted three times with the same process to ensure uniform chemical composition;
[0059] C. After the melt obtained by the treatment in step B solidifies and forms, perform the last smelting: after the melt is evenly melted, reduce the current from 550A to 450A, and then reduce the current by 30A every 10s; when it is reduced to 300A, start to slowly lift the tungsten arc gun away from the molten pool and stop it at the edge of the crucible until the current is reduced to 150A, stop retracting the gun, reduce the current to 0A, and turn off the power;
[0060] D. After smelting, cool to room temperature to obtain TiAl alloy ingot.
[0061] Among them, if the pressure in the furnace is lower than 0.05Pa after high-purity argon is filled in step (2), the various elements of the alloy components become easy to volatilize due to the existence of saturated vapor pressure during the smelting process; specifically, since the saturated vapor pressure of the Al element is relatively large, it is easier to volatilize; this causes the alloy composition after the final solidification to deviate from the nominal composition, affecting the microstructure and mechanical properties of the alloy. If the pressure in the smelting furnace is higher than 0.05Pa after argon is filled, the heat generated during the smelting process will increase the pressure in the furnace, resulting in air leakage in the furnace, which will increase the oxygen content and have an adverse effect on the alloy. In step C, by making "the current reduce by 30A every 10s" (until the current is 300A), the purpose of this is to keep the current decreasing at a uniform rate, so that the temperature drop of the alloy solution itself is also uniform; "when it is reduced to 300A, start to slowly lift the tungsten arc gun away from the molten pool and stop it towards the edge of the crucible". The purpose of this is to slowly raise the arc gun away from the molten pool. The top of the alloy ingot is the last area to solidify, which can avoid the formation of pits due to the blowing force of the arc gun, and ensure that the top morphology of the alloy ingot is flat and smooth.
[0062] The present invention also proposes a high-plasticity TiAl alloy, and the high-plasticity TiAl alloy of the embodiment of the present invention is obtained by processing using the method described above. The high-plasticity TiAl alloy of the present invention has a room temperature structure in which a network structure composed of nano B2 phases coupled with recrystallized γ grains surrounds a small lamellar cluster (this special structure produces back stress strengthening when deformed by force, which helps to reduce the concentration of stress in a single component phase or phase interface, and promotes the plastic deformation ability of the coordinated alloy), and has considerable room temperature and high temperature mechanical properties compared to the original cast alloy, and the room temperature plasticity is significantly increased.
[0063] In the following examples: all raw materials are from Beijing Yanbang New Material Technology Co., Ltd., where Ti particles are 4N 3×3mm, Al particles are 4N 3×3mm, Cr particles are 3N 3-10mm, Re powder is 4N-325 mesh, and Ru powder is 4N-325 mesh. Titanium particles are made by drawing and forging after sponge titanium consumable smelting, aluminum particles are made by electrolytic ingot preparation and remelting and drawing, chromium particles are obtained by electrolytic chromium block crushing, and Re powder and Ru powder are obtained by redox reaction.
[0064] Example 1
[0065] The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation in this embodiment includes the following steps:
[0066] Step 1: Calculate the raw material content by atomic percentage, where Al is 48%, Cr is 3%, Re is 0.8%, Ru is 1%, and the balance is Ti. Weigh titanium sponge particles, high-purity Al particles (particle size is 2-3mm, purity is 99.99wt.%), high-purity Cr particles (particle size is 1-2mm, purity is 99.99wt.%), high-purity Re powder (purity is 99.999wt.%) and high-purity Ru powder (purity is 99.999wt.%), with a total atomic percentage of 100%. Screen and classify the weighed raw materials, and dry the particles in a drying oven to prevent the accompanying water vapor or other impurities from affecting the smelting process.
[0067] Step 2: Melting
[0068] ① Due to the large difference in melting point between Al and other elements such as Re and Ru, the burning loss of Al is inevitable during the heating process. Therefore, the compensation amount of Al is set to 2wt.% of its added mass during the raw material configuration. The weighed Re powder and Ru powder are wrapped with aluminum foil and placed at the bottom of the water-cooled copper crucible to prevent them from being blown off by the tungsten arc gun during smelting. Small Al particles and Cr particles are spread on top of the Re powder and Ru powder, and finally a larger sponge titanium block is placed on the upper part of the crucible. Aim the arc gun at the raw material to be smelted, close the arc furnace door, and turn on the circulating cooling water. The raw materials are melted and TiAl alloy ingots are prepared using non-consumable vacuum arc melting technology.
[0069] ② Vacuum treatment: Turn on the power of the multifunctional arc melting system, and use a mechanical pump and a high-speed molecular pump to pump the vacuum degree in the furnace to 3×10 -3 Pa, and wait until the vacuum degree drops to 3×10 -3 Pa, stop running the molecular pump, turn off the vacuum gauge, and after the molecular pump speed reaches 0, fill the furnace with high-purity argon until the pressure inside the furnace reaches 0.05 Pa. Filling with argon can not only remove the residual oxygen in the furnace, but also ionize and start the arc.
[0070] ③ Arc-starting and heating melting: After the operation is ignited, the current is increased from 30A to 150A to soften the raw materials and connect them to each other. Then evenly increase it to 550A to make all the raw materials completely melted and form a uniform melt. Subsequently, the current is slowly reduced to 0A, the smelting power supply is turned off, and the first smelting is completed. After the alloy solidifies and forms, the ingot is turned over by a turning spoon, and the smelting is repeated 3 times with the same process to ensure that the chemical composition of the alloy is uniform. After the ingot solidifies, the last smelting is carried out. First, slowly increase the current to 550A to ensure that the alloy is completely melted, and then reduce the current to 450A and start timing. The current is reduced by 30A every 10s. When the current is reduced to 300A, the tungsten arc gun is slowly lifted away from the molten pool and docked at the edge of the crucible. When the current is reduced to 150A, stop collecting the gun, reduce the current to 0A, and turn off the power supply. After smelting is completed, when the alloy ingot is cooled to room temperature, the furnace door is opened to take out the alloy ingot, the arc furnace is cleaned, the furnace door is closed, the vacuum is re-evacuated to a negative pressure state, and the circulating cooling water is turned off. The original cast TiAl alloy ingot is prepared.
[0071] Step 3: Determine the compression deformation temperature: Use differential scanning calorimetry to analyze the TiAl alloy sample obtained in step 2 and measure the transformation temperature T of the γ→α phase. e Its upper and lower temperature limits (T e is 1250°C, its upper limit temperature is 1280°C and its lower limit temperature is 1230°C).
[0072] Step 4, isothermal / variable temperature compression deformation: Use wire cutting to cut several cylindrical specimens with a diameter of 8 mm and a height of 12 mm from the alloy ingot melted in step 2. Use sandpaper to grind off the wire cutting marks on the side and upper and lower end faces of the cylinder, and then clean it with ultrasonic waves and dry it. Weld two thermocouples, the positive and negative electrodes, at the center of the height direction of the cylindrical specimen. Place the specimen in a heating furnace, with the upper and lower end faces of the cylinder close to the nickel-based alloy pads respectively. After the vacuum degree in the heating furnace on the universal testing machine reaches the standard, increase the temperature in the furnace to 1200°C at a rate of 7°C / s. After keeping the specimen at this temperature for 20 minutes, adjust the compression rate to 0.01s. -1 , prepare to start compression deformation. When the sample height drops by 25%, stop compression, take out the sample and air cool it.
[0073] Step 5. After the temperature in the furnace drops to 1150°C, put the alloy sample that has been cooled to room temperature back into the heating furnace. After keeping warm for 20 minutes, continue to press down 25% of the original height of the sample at the same compression rate. After the compression is completed, take out the sample for air cooling. After the temperature in the furnace drops to 1100°C, 1050°C and 950°C respectively, repeat the above operation, but reduce the pressing amount to 15%, 10% and 5% respectively. After the isothermal compression at 950°C is completed, take out the alloy sample and air cool it to room temperature. The deformed alloy is prepared and the high-plasticity TiAl alloy of this embodiment is obtained. The highly high-plasticity TiAl alloy obtained in this embodiment is reduced by 80% relative to the original height of the sample (the original height of the sample is 12mm). Turn off the computer and then turn off the universal testing machine.
[0074] Example 2
[0075] The difference between this embodiment and embodiment 1 is that the temperature rise rate, heating time, and holding time in the universal testing machine described in step 4 must be set on the computer program side, and the pressing amount is converted into a true strain value and input into the calculation program. Two platinum-rhodium thermocouples are welded to the middle of the cylindrical sample by a spot welder to ensure accurate measurement of temperature changes during the hot compression process, and the other ends of the two thermocouples are connected to the electrodes on the thermal-mechanical simulation testing machine. The rest is the same as embodiment 1.
[0076] Example 3
[0077] Figure 1 This is a flow chart of a method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation according to an embodiment of the present invention. Figure 1 , the temperature was raised to 1200°C at a rate of 10°C / s, the prepared TiAl alloy cylindrical sample (the same as in Example 1) was kept warm for 20 minutes, then pressed down by 25% in the height direction, and then air-cooled to room temperature. On this basis, the cooled alloy sample was kept warm at 1150°C for 20 minutes, continued to be pressed down by 25% of the original height, and then air-cooled to room temperature; on this basis, the alloy sample was kept warm at 1100°C, 1050°C, and 950°C for 20 minutes, and then pressed down by 15%, 10%, and 5% of the original height, respectively, according to the above steps, so that the total pressing amount reached 80% or more, and the sample was air-cooled to room temperature after each compression deformation.
[0078] Example 4
[0079] The only difference between this embodiment and embodiment 1 is that in step 1, the raw material contents are calculated by atomic percentage, Al is 46%, Cr is 3%, Re is 0.8%, Ru is 1%, and the balance is Ti; the rest is the same as embodiment 1.
[0080] Example 5
[0081] The difference between this embodiment and embodiment 1 is that in step 1, the raw material contents are calculated by atomic percentage, Al is 50%, Cr is 3%, Re is 0.8%, Ru is 1%, and the balance is Ti; the rest is the same as embodiment 1
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 1 is that in step 4, the TiAl alloy is heated to 1200°C and kept at this temperature for 20 minutes, and then heated to 0.01s -1 The compression rate is 80%, the sample height decreases by 80% relative to that before compression, and the alloy undergoes a compression deformation (step five is omitted); the rest is consistent with Example 1.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 1 is that in step 4 and step 5, the compression ratio is 16% each time (each compression decreases 16% relative to the original height of the sample); the rest is consistent with Example 1.
[0086] Comparative Example 3
[0087] The difference between this comparative example and Example 1 is that in step 4 and step 5, after each compression, the step of cooling the sample to room temperature is omitted, and after the sample is compressed in the previous step, the next compression is directly carried out after the temperature in the furnace is reduced to the next set value and kept warm for 20 minutes; the rest is consistent with Example 1.
[0088] Comparative Example 4
[0089] The difference between this comparative example and Example 1 is that in step 4 and step 5, the sample is cooled to room temperature by water cooling after each compression; the rest is consistent with Example 1.
[0090] Experimental example
[0091] 1. The original cast TiAl alloy (rectangular specimen, 8 mm in length, 6 mm in width, 4 mm in thickness) and the compressed TiAl alloy obtained by smelting in step 2 were cut by wire cutting technology for organization observation. The surface to be observed was polished to 2000# with sandpaper, and ultrasonic cleaning and drying were performed after mechanical polishing. The microstructure of the TiAl alloy obtained after the first, first two, first three, first four, and total five compression deformations was observed under a scanning electron microscope.
[0092] Figure 2 (a) is the temperature of Comparative Example 1 at 1200°C and 0.01s -1The macrostructure of the TiAl alloy obtained by a compression deformation of 80% at a strain rate of Figure 2 (b) is the value in Example 1 at 0.01s -1 The macrostructure of the TiAl alloy after multi-step cooling / isothermal compression at a strain rate of . By comparison, it can be seen that after a large-scale compression deformation, the edge of the alloy suffers from severe shear cracking, while the TiAl alloy after multi-step cooling / isothermal compression still has a complete edge, which shows that the method provided by the present invention ensures that the alloy has the ability to continue plastic deformation without cracking.
[0093] Figure 3 (a) is the macrostructure of the TiAl alloy obtained after five times of compression deformation at the same ratio in Comparative Example 2, Figure 3 (b) is the value in Example 1 at 0.01s -1 The macrostructure of the TiAl alloy after multi-step cooling / isothermal compression at a strain rate of . By comparison, it can be seen that the edges of the TiAl alloys that undergo the same compression ratio deformation at different temperatures still have a tendency to crack, while the edges of the TiAl alloys that undergo multi-step cooling / isothermal compression have a complete outline. The alloy prepared by the method of the present invention has the characteristics of uniform plastic deformation.
[0094] Figure 4 (a) is a microstructure photograph of the original cast TiAl alloy obtained by smelting in step 2 in Example 1, Figure 4 (b) Yes Figure 4 (a) Local magnified image of the red box area. The original cast TiAl alloy is mainly composed of coarse lamellar clusters and coupled γ phase and B2 phase. The average lamellar size is measured to be about 85.20μm, and the average size of the banded B2 phase is 10.70-14.20μm. A large number of banded B2 phases are distributed along the lamellar cluster boundaries, dividing the lamellar matrix.
[0095] Figure 5 is a microstructure photograph of the TiAl alloy obtained by isothermal compression at 1200° C. in Example 1-3 (compressed by 25% relative to the original cast TiAl alloy), Figure 5 (b) Yes Figure 5 (a) The local magnified image of the red box area. The original cast TiAl alloy was heated at 1200℃ for 0.01s -1After being pressed down 25% in the height direction at a strain rate of , the lamellar layer twisted and bent, and the microstructure was significantly refined. The size of the lamellar cluster was 72.50μm. The original banded B2 phase split and broke, and was no longer continuously distributed on the lamellar cluster boundary. Its average size was about 5.35μm. The equiaxed γ phase was slightly recrystallized. The TiAl alloy after compression deformation is still composed of lamellar clusters, B2 phase and equiaxed γ phase.
[0096] Figure 6 The microstructure of the TiAl alloy obtained after the temperature is lowered to 950°C and the alloy is further compressed by 5% of the original height based on four isothermal compressions at 1200°C, 1150°C, 1100°C and 1050°C in Example 1-3. Figure 6 (b) Yes Figure 6 (a) A local enlarged view of the red box area. Figure 6 (c) is a transmission electron microscope image of the highly plastic TiAl alloy obtained after 5 compression deformations.
[0097] Depend on Figure 6 It can be seen that after five isothermal compressions, the alloy did not crack, but underwent uniform plastic deformation. In the direction perpendicular to the compression, the microstructure has a network structure, the lamellar cluster size is about 37.70μm, the average size of the B2 phase is 0.92μm, and the average size of the equiaxed γ phase is 1.33μm. The nanoscale B2 phase and the fine equiaxed γ phase are alternately distributed around the lamellar clusters, forming a strong size difference with the lamellar clusters. Through the method of multiple cooling / isothermal superimposed compression deformation, the B2 phase can be greatly refined to the nanoscale while slightly refining the lamellar cluster size. This multi-size component phase promotes the significant diffusion of dislocations and realizes stress redistribution. It has the effect of synergistic strengthening and alleviating strain localization during the deformation process. From Figure 6 In (c), it is observed that there are abundant dislocations and nanotwins around the lamellar clusters and nano B2 phases. The aggregation and recovery of dislocations can promote the transformation of B2 phase and γ grains into recrystallization or substructures during the subsequent plastic deformation process. During the continuous isothermal / cooling plastic deformation process, defects such as dislocations and nanotwins are retained, and new dislocations and nanotwins are activated and nucleated on existing defects, releasing excessive deformation stress, which is beneficial to improving the ductility of the alloy.
[0098] 2. Use wire cutting technology to cut three samples of room temperature compression and high temperature tensile from the TiAl alloy to be tested, and test the mechanical properties on an electronic universal testing machine. Each mechanical property is tested three times to reduce the experimental error. The compression rate selected for room temperature compression is 0.5mm / min; the high temperature tensile test is performed at 850℃ (this temperature is lower than 950℃, which can retain the high-density micro-nano defects accumulated after deformation, and is at the corresponding service temperature of TiAl alloy), and the tensile rate is set to 0.3mm / min.
[0099] Figure 7 The graphs are room temperature compression and 850°C high temperature tensile performance diagrams of the original cast TiAl alloy, the TiAl alloys of Comparative Examples 1-4, and the TiAl alloy after compression deformation (80% compression relative to the original cast TiAl alloy) in Example 1.
[0100] from Figure 7 It can be seen from (a) that the compressive strength of the TiAl alloy prepared in Example 1 is increased from 1919.4MPa to 2536.5MPa, and the compressive strain is increased from 32.9% to 42.6% compared with the original cast alloy (the performance of the strong plastic TiAl alloy obtained in Examples 2 and 3 is equivalent to that of Example 1). The room temperature compressive performance of the TiAl alloy prepared in Comparative Examples 1 and 2 is even lower than that of the original cast alloy. For Comparative Example 1, the reduction in room temperature compressive performance is due to the fact that the stress caused by the high compression ratio exceeds the bearing capacity of the alloy. Even if micro defects are formed, their beneficial effects are suppressed by severe stress concentration, and the alloy cracks. For Comparative Example 2, due to the gradual decrease in compression temperature, the ability of the alloy to undergo plastic deformation is also reduced. When the same compression ratio is used, more severe stress concentration will often be formed at low temperatures. These stress concentration areas are also where cracks initiate and expand, and the compressive strength and compressive strain of the alloy cannot be further improved. For comparative example 3, the alloy was compressed to the next compression temperature before being cooled to room temperature, which would cause the alloy to crack during the cooling process due to uneven internal and external temperatures. This deformation mode aggravated the coarsening of the grains and made the alloy brittle. For comparative example 4, the alloy was water-cooled to room temperature. Compared with air cooling, the internal stress of the alloy was larger and the compression performance was relatively reduced.
[0101] from Figure 7As can be seen in (b), compared with the original cast alloy, the tensile strength of the deformed TiAl alloy at 850°C is increased from 403.5MPa to 505.7MPa, and the elongation is increased from 3.5% to 5.3%. Since the multi-step isothermal / variable temperature compression deformation integrates heat treatment and thermal deformation, rich substructures and defects are introduced when the microstructure changes with deformation, which is more conducive to dislocation slip and multi-configuration coordinated deformation of the alloy during deformation. In addition, as the deformation temperature decreases, the amount of deformation applied to the alloy also decreases. This more gentle plastic deformation method can ensure that the alloy completes large plastic deformation without cracking. The microstructure with a reticular structure finally obtained does contain high-density defects. This heterogeneous structure not only improves the room temperature and high temperature strength of the alloy by producing a back stress strengthening effect, but also retains good plasticity. The tensile strength and elongation of the TiAl alloys prepared in Comparative Examples 1, 2, 3 and 4 are relatively reduced.
[0102] The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superimposed deformation provided by the present invention can promote the diversification of process parameter design and preparation process of TiAl alloy in the field of hot processing, and provide a new idea for promoting the application and promotion of TiAl alloy in military engineering fields such as aerospace, automobiles and aircraft in the future.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation, characterized in that: The method comprises the following steps: performing multiple axial compressions on a sample of a TiAl alloy ingot; heating the sample to a set temperature and keeping the temperature before each compression, and then compressing the sample, and cooling the sample to room temperature after each compression; As the number of compressions increases, the set temperature gradually decreases, the compression ratio gradually decreases, or the compression ratio first remains unchanged and then gradually decreases.
2. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation as claimed in claim 1, characterized in that: The set temperature is the transition temperature T of the sample from the γ phase to the α phase e Temperature values below the lower limit temperature; The cooling method is air cooling.
3. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation as claimed in claim 1, characterized in that: The number of compressions is 3-7 times, the difference in set temperature between two adjacent compressions is 10-100°C; the difference in ratio between two adjacent compressions is 0-15%, and the difference in ratio between two adjacent compressions increases first and then decreases as the number of compressions increases.
4. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation as claimed in claim 3, characterized in that: The set temperatures are 1170-1220°C, 1130-1170°C, 1080-1130°C, 1030-1080°C and 930-980°C as the number of compressions increases; Calculated based on the initial height of the sample, the compression ratios are 22%-27%, 22%-27%, 12%-17%, 7%-12% and 3%-7% as the number of compressions increases.
5. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation as claimed in claim 1, characterized in that: The compression rate for each compression is 0.001-0.05s -1 ; The insulation time is 10-30 minutes.
6. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation as claimed in claim 1, characterized in that: The heating and compression are performed under vacuum conditions in a heating furnace of a universal testing machine.
7. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation as claimed in claim 6, characterized in that: The sample is cylindrical, a positive thermocouple and a negative thermocouple are welded on the sample, and the upper and lower end surfaces of the sample are respectively in close contact with the nickel-based alloy pad of the universal testing machine; In the height direction of the sample, the positive thermocouple and the negative thermocouple are arranged at the center position of the sample.
8. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation according to any one of claims 1 to 7, characterized in that: The element composition of the TiAl alloy ingot includes, in atomic percentage, 46%-50% Al, 2%-6% Cr, 0.2%-1.2% Re and 0-2% Ru.
9. The method for improving the strength and plasticity of TiAl alloy based on cooling and isothermal superposition deformation as claimed in claim 8, characterized in that: The TiAl alloy ingot is obtained by vacuum arc melting; The raw materials of the TiAl alloy ingot include: Sponge particles or sponge blocks; Al particles, wherein the Al particles have a particle size of 2-3 mm and a purity of 99.99 wt.%; Cr particles, wherein the particle size of the Cr particles is 2-3 mm and the purity is 99.99 wt.%; Ru powder, wherein the purity of the Ru powder is 99.999wt.%; Re powder, wherein the purity of the Re powder is 99.999wt.%.
10. A high-plasticity TiAl alloy, characterized in that: The high-plasticity TiAl alloy is obtained by processing using the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Novel heat-resisting titanium alloy and processing and manufacturing method and application thereof
CN104018027A
Mechanical heat treatment method for obtaining duplex microstructures of metastable beta titanium alloys
CN109321855A
Reinforced and toughened metastable beta titanium alloy and preparation method thereof
CN113278849A
Manufacturing method for improving welding seam strength of titanium alloy welding part
CN117888047A
Cited By
Regulation and control method for inhibiting hard and brittle phases and improving room-temperature plasticity of TiAl alloy
CN122609990A
